Sistem Informasi Usaha Mikro Kecil Dan Menengah Kain Tenun Di Umma Kabba Sumba Barat - Sesilia Apliana Mawo Naga; Stefanus D.I.Mau; Karolus Wulla Rato (GLOBAL SCIENTS PUBLISHER, 2026)
The development of information technology opens up strategic opportunities for micro, small, and medium enterprises (MSMEs) to strengthen their competitiveness and expand market access, particularly in the creative economy sector based on local wisdom, such as woven fabric MSMEs. However, woven fabric MSMEs in Umma Kabba, West Sumba, still face significant obstacles in the form of limited marketing strategies and low sales revenue due to their reliance on conventional sales methods. This situation demands a technology-based solution capable of improving marketing effectiveness and sales performance. This study aims to implement an information system in woven fabric MSMEs in Umma Kabba and analyze the impact of this implementation on increasing sales revenue. The study used an applied approach with a systematic information system development method. Data were collected through observation, interviews, and documentation to identify system requirements and compare conditions before and after implementation. The research stages included needs analysis, design, implementation, and system testing. The results show that the information system improves data management efficiency, expands marketing reach, improves interactions with consumers, and significantly increases sales revenue and business sustainability.